Iron dextran and iron dextran-gentamycin combined, compared as methods of preventing iron-deficiency anemia in neonatal pigs - D A Schoneweis; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1977)
Giving an iron iron dextran-gentamycin combination to young pigs had no advantages over giving them iron dextran alone, as measured by hemoglobin levels, packed cell volumes, or weight (when 28 days old).; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Iron dextran; Iron dextran-gentamycin; Iron-deficiency anemia; Neonatal pigs